Brain region-specific effects of immobilization stress on cholinesterases in mice. (2nd January 2017) - Valuskova, Paulina; Farar, Vladimir; Janisova, Katerina; Ondicova, Katarina; Mravec, Boris; Kvetnansky, Richard; Myslivecek, Jaromir
Abstract: Brain acetylcholinesterase (AChE) variant AChER expression increases with acute stress, and this persists for an extended period, although the timing, strain and laterality differences, have not been explored previously. Acute stress transiently increases acetylcholine release, which in turn may increase activity of cholinesterases. Also the AChE gene contains a glucocorticoid response element (GRE), and stress-inducible AChE transcription and activity changes are linked to increased glucocorticoid levels. Corticotropin-releasing hormone knockout (CRH-KO) mice have basal glucocorticoid levels similar to wild type (WT) mice, but much lower levels during stress. Hence we hypothesized that CRH is important for the cholinesterase stress responses, including butyrylcholinesterase (BChE). We used immobilization stress, acute (30 or 120 min) and repeated (120 min daily × 7) in 48 male mice (24 WT and 24 CRH-KO) and determined AChER, AChE and BChE mRNA expression and AChE and BChE activities in left and right brain areas (as cholinergic signaling shows laterality). Immobilization decreased BChE mRNA expression (right amygdala, to 0.5, 0.3 and 0.4, × control respectively) and AChER mRNA expression (to 0.5, 0.4 and 0.4, × control respectively). AChE mRNA expression increased (1.3, 1.4 and 1.8-fold, respectively) in the left striatum (Str). The AChE activity increased in left Str (after 30 min, 1.2-fold), decreased in right parietal cortex with repeated stress (to 0.5 × control). BChE activity decreased after 30 min in the right CA3 region (to 0.4 × control) but increased (3.8-fold) after 120 min in the left CA3 region. The pattern of changes in CRH-KO differed from that in WT mice.